COVID-19 vaccination coverage among adolescents aged 12–17 years in three provinces of eastern China: A cross-sectional survey, 2021 - Li, Taishun; Qi, Ruowen; Chen, Bingwei; Luo, Yuqian; Zhang, Wenjun; Zhou, Yi-Hua; Xu, Biyun (Frontiers in Public Health, 2022)
High vaccination coverage is essential to prevent and control the spread of the COVID-19 epidemic. Currently, the real-world acceptance of COVID-19 vaccines among adolescents aged 12–17 years in China has not been reported. We aimed to assess the acceptance rate of COVID-19 vaccination among adolescents in eastern China and to identify factors associated with the intention to get vaccinated against COVID-19. We conduct a cross-sectional questionnaire survey among adolescents from three provinces in the eastern part of China from 16 August to 28 October 2021. The questionnaires were distributed to 2,100 students, and 2,048 students completed the questionnaires. The results showed that 98.4% (2,016/2,048) of adolescents had received at least one dose of the COVID-19 vaccine and 1.6% (32/2,048) declined the vaccination. The participants from rural districts, or whose parents were vaccinated, were more likely to accept the vaccine. The main reason for declining vaccination was worry about vaccine safety (25%). The main adverse event after the vaccination was pain at the injection site. In conclusion, the vaccine coverage rate reached 98.4% among the adolescents in this study, which met the criteria for herd immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The high vaccination rate is beneficial to the prevention and control of the COVID-19 pandemic.